Determinants of In-hospital Mortality in Preterm Neonates Admitted to a Tertiary Indonesian NICU: A One-Year Retrospective Cohort of 209 Infants - Komang Okky Maharani Ciptana Putri; Putu Mas Vina Paramitha Cempaka; I Made Kardana; Made Sukmawati; Putu Junara Putra; I Wayan Dharma Artana (HM Publisher, 2026)
Background. Preterm birth is the largest single contributor to global neonatal mortality, and Southeast Asia carries a disproportionate burden, yet contemporary multivariable data from Indonesian tertiary neonatal intensive care units (NICUs) remain limited. We aimed to identify maternal, perinatal and neonatal determinants of in-hospital mortality among preterm neonates at the NICU of Prof. I.G.N.G Ngoerah Hospital, Denpasar, Bali. Methods. In a single-centre retrospective cohort, 209 preterm neonates (gestational age <37 weeks and birth weight <2500 g) admitted between September 2024 and September 2025 were enrolled by total sampling. Bivariate logistic regression with p<0.25 inclusion threshold was followed by multivariable binary logistic regression; intermediate-outcome variables (RDS and surfactant therapy) were excluded a priori to avoid over-adjustment bias. Results. In-hospital mortality was 42.1% (88/209) and decreased monotonically across birth-weight strata, from 75.0% in infants <1000 g to 41.9% in 1000–1499 g and 22.9% in ≥1500 g (Cochran–Armitage trend p<0.001). Sepsis (56.8%) and respiratory distress syndrome (30.7%) accounted for 87.5% of deaths. In the multivariable model, birth weight 1000–1499 g (adjusted odds ratio [aOR] 0.36, 95% CI 0.15–0.90; p=0.029) and ≥1500 g (aOR 0.17, 95% CI 0.06–0.51; p=0.001) and each 1-point increment in 5-minute Apgar score (aOR 0.81, 95% CI 0.67–0.98; p=0.031) were independently associated with lower mortality. Maternal urinary tract infection trended toward higher mortality (aOR 2.85, 95% CI 0.97–8.35; p=0.057). Conclusion. Birth weight and 5-minute Apgar score are independent, immediately measurable predictors of in-hospital preterm mortality in this Indonesian tertiary NICU. Combining bedside risk stratification with antenatal corticosteroid coverage audit and universal antenatal urine-culture screening offers a translational pathway to reduce neonatal mortality in resource-constrained Southeast Asian settings.